Large-scale identification of protein histidine methylation in human cells. (22nd May 2021) - Kapell, Sebastian; Jakobsson, Magnus E
Abstract: Methylation can occur on histidine, lysine and arginine residues in proteins and often serves a regulatory function. Histidine methylation has recently attracted attention through the discovery of the human histidine methyltransferase enzymes SETD3 and METTL9. There are currently no methods to enrich histidine methylated peptides for mass spectrometry analysis and large-scale studies of the modification are hitherto absent. Here, we query ultra-comprehensive human proteome datasets to generate a resource of histidine methylation sites. In HeLa cells alone, we report 299 histidine methylation sites as well as 895 lysine methylation events. We use this resource to explore the frequency, localization, targeted domains, protein types and sequence requirements of histidine methylation and benchmark all analyses to methylation events on lysine and arginine. Our results demonstrate that histidine methylation is widespread in human cells and tissues and that the modification is over-represented in regions of mono-spaced histidine repeats. We also report colocalization of the modification with functionally important phosphorylation sites and disease associated mutations to identify regions of likely regulatory and functional importance. Taken together, we here report a system level analysis of human histidine methylation and our results represent a comprehensive resource enabling targeted studies of individual histidine methylation events. Graphical Abstract: